The 1629 Acehnese Invasion of Malacca: A Eurasian Perspective - Wijaya, Daya Negri (History Department, Semarang State University and Historian Society of Indonesia, 2022)
The rising tension in the Straits of Malacca in the first half of the 17th century forced the political entities to make an ally on one side and invade other states on the other side. Acehnese Sultanate succeeded in capturing all Malay states, except for Malacca. The desire to control the straits forced them to make an assault. Interestingly, the 1629 Acehnese siege of Malacca was perceived differently. The Acehnese chronicles seem to be quiet except for the Bustan Al-Salatin. However, the European sources are proud to explain the Portuguese victory over the greatest fleet in Asia. The available Eurasian sources should be exploited to cross-check the historical data and narrate more accurately. The siege started when the Acehnese were anchored and fortified. However, they succeeded in surrounding the fortress for a month, but the Luso-Malay joint forces could counter-attack and drive them out from Malacca. The Portuguese relief forces continued to patrol the straits after the Acehnese failure. Unfortunately, the death of Nuno Alvares Botelho in the tragedy of the Dutch ship’s explosion forced the Portuguese to bury their dream of securing the mercantile route of India and China from the Dutch threat. Meningkatnya tensi di Selat Melaka di pertengahan paruh pertama abad 17 telah mendorong entitas politik untuk membuat sekutu dalam satu sisi dan melakukan invasi pada negara lain pada sisi yang lain. Kesultanan Aceh berhasil mencaplok semua negara Melayu kecuali Melaka. Keinginan kuat untuk mengontrol selat memaksa mereka untuk melakukan serangan. Menariknya, penyerbuan Aceh di Melaka tahun 1629 dilihat secara berbeda. Hikayat-hikayat Aceh terlihat diam kecuali the Bustan Al-Salatin, tetapi sumber Eropa dengan bangga menjelaskan kemenangan Portugis atas armada terbesar yang pernah ada di Asia. Ketersediaan sumber-sumber Eropa dan Asia seharusnya dieksploitasi bukan hanya untuk proses verifikasi sumber data tetapi juga untuk menarasikan lebih akurat. Penyerbuan dimulai ketika Aceh mendarat dan membuat benteng. Walaupun mereka, berhasil mengepung benteng Melaka selama sebulan tetapi pasukan gabungan Luso-Melayu dapat memukul balik and menendang mereka keluar. Pasukan penyelamat Portugis terus melanjutkan tugasnya untuk melakukan patroli di selat setelah kegagalan Aceh. Sayangnya, kematian Nuno Alvares Botelho dalam tragedi meletusnya kapal Belanda memaksa orang-orang Portugis mengubur impiannya untuk mengamankan jalur perdagangan India dan China dari ancaman Belanda. Cite this article: Wijaya, D.N. (2022). The 1629 Acehnese Invasion of Malacca: A Eurasian Perspective. Paramita: Historical Studies Journal, 32(2), 221-229. http://dx.doi.org/10.15294/paramita.v32i2.36883